Clinical and psychological profiles of patients with different patterns of nonsuicidal self-injury - Zinchuk, Mikhail; Kustov, Georgii; Mishin, Ilya; Popova, Sofya; Sviatskaia, Ekaterina; Yakovlev, Alexander; Guekht, Alla (Frontiers in Psychiatry, 2025)
IntroductionSuicide remains a significant public health problem worldwide, particularly in Eastern European countries. Previous studies have shown that nonsuicidal self-injury (NSSI) is one of the most important risk factors for suicide attempts, particularly among people with mental disorders. At the same time, the risk of various dramatic outcomes, including suicide, is likely to vary among different NSSI subtypes. The aim of this study was to evaluate the relationships between NSSI parameters and clinical/psychological variables in Russian patients with non-psychotic mental disorders and suicidal ideation.MethodsThe Inventory of Statements About Self-Injury-1 (ISAS) was translated and adapted in the sample of Russian patients with NSSI. The study sample consisted of 614 consecutively enrolled patients with NSSI and suicidal ideation. The data were clustered based on the method and frequency of NSSI, and the relationships between frequency and method patterns and other NSSI parameters (age at onset of NSSI, experience of physical pain during NSSI, etc.), clinical characteristics (anxiety and depression levels, psychiatric diagnosis), psychological profiles, and quality of life were evaluated.ResultsCluster analysis identified three subtypes of NSSI. Patients with a greater frequency and variety of methods of NSSI attempted suicide more often, were more clinically severe, had significantly higher scores on most pathological personality traits, had less resilience to suicide, and had a lower quality of life.DiscussionOur findings support the need for a high level of clinical attention to people with mental disorders who frequently engage in NSSI using a variety of methods. The significant differences in many of the parameters studied between the other two clusters highlighted the importance of further research into the typologization of NSSI behavior, which could lead to increased certainty in the prognosis of NSSI patients and become the basis for targeted therapy.